The prevalence of neural tube defects and the outcome of myelomeningocele in Cape Town - Buccimazza, Sandro Sabatino (Department of Paediatrics and Child Health, 2017)
This study was designed to document the prevalence of neural tube defects in Cape Town and to determine the outcome of children born with a myelomeningocele and operated on within the Neurosurgical service of the University of Cape Town. The aim of the prevalence study was to document the frequency of neural tube defects (NTD) over a twenty year period in Cape Town (1973 - 1992) and to determine the effects of race, gender, maternal age, parity, and season of conception on the prevalence. Multiple sources of ascertainment were used, including all maternity hospital records, neurosurgical and spinal defects clinic data, as well as those from the Human Genetics Department and Fetal Abnormality Group. The prevalence rates for NTD fluctuated between 1,74 and 0,63 per 1 000 births, but showed no significant trends over the twenty year period. Prevalence rates were highest for the white population group at 2,56 per 1 000 births compared to 0,95 per 1 000 for blacks and 1,05 per 1 000 for those of mixed ancestry. The higher rates in the whites, who are of British and European extraction and belong to the more affiuent section of the community, would suggest that the possible effects of nutrition and infection are overshadowed by genetic factors. There was a female preponderance for both spina bifida (M:F ratio 0,89) and anencephaly (M:F ratio 0,67). The highest NTD rates were found at both ends of the maternal age range (<20 years and >35 years of age). The prevalence was highest at the extremes of birth order (1,65 and 1,58 for birth order 1 and >7, respectively, and 0,56 and 0,45 for birth order 5 and 6, respectively). A seasonal variation occurred which differed from that reported for the Northern Hemisphere and may reflect local climatic conditions. The aim of the outcome study was to follow a group of infants who were operated on for myelomeningocele (01 January 1979 - 31 December 1985) and evaluate their outcome at five years of age, in an attempt to identify factors that may influence the quality of survival and their outcome, and to utilise these findings to recommend altering and improving ( where possible) the management of children born with myelomeningocele.